Mining the language of the "rush" for gold in the 19th century. (March 2022) - Carpenter, Lloyd; Fields, Alison
This research seeks to identify newspapers' contribution to the construction of the language describing the era now popularly termed the "gold rush." We examine the early narratives of the first golden finds, tracing how these ignited a conflagration which would impact the whole world and examining the unique contribution made by the Hawai'ian Polynesian newspaper to spread the news to Australasia, the American East Coast, and even Great Britain. Employing text-mining tools offers a way of uncovering the language used in context and at source over the past two centuries, and to provide an overarching view of the language of the rush for gold. Text-mining tools and primary source newspapers are used to identify this contribution and the startling conclusion that the world experienced, not a rush for gold, but a fever, a mania, and even an excitement.